First ROV Exploration of the Perth Canyon: Canyon Setting, Faunal Observations, and Anthropogenic Impacts - Trotter, Julie A.; Pattiaratchi, Charitha; Montagna, Paolo; Taviani, Marco; Falter, James; Thresher, Ron; Hosie, Andrew; Haig, David; Foglini, Federica; Hua, Quan; McCulloch, Malcolm T. (Frontiers in Marine Science, 2019)
This study represents the first ROV-based exploration of the Perth Canyon, a prominent submarine valley system in the southeast Indian Ocean offshore Fremantle (Perth), Western Australia. This multi-disciplinary study characterises the canyon topography, hydrography, anthropogenic impacts, and provides a general overview of the fauna and habitats encountered during the cruise. ROV surveys and sample collections, with a specific focus on deep-sea coral, were conducted at six sites extending from the head to the mouth of the canyon. Multi-beam maps of the canyon topography show near vertical cliff walls, scarps, and broad terraces. Biostratigraphic analyses of the canyon lithologies indicate Late Paleocene to Late Oligocene depositional ages within upper bathyal depths (200-700 m). The video footage has revealed a quiescent ‘fossil canyon’ system with sporadic, localised concentrations of mega- and macro-benthos (~680-1800 m), which include corals, sponges, molluscs, echinoderms, crustaceans, brachiopods, and worms, as well as plankton and nekton (fish species). Solitary (Desmophyllum dianthus, Caryophyllia sp., Vaughanella sp., and Polymyces sp.) and colonial (Solenosmilia variabilis) scleractinians were sporadically distributed along the walls and under overhangs within the canyon valleys and along its rim. Gorgonian, bamboo, and proteinaceous corals were present, with live Corallium often hosting a diverse community of organisms. Extensive coral graveyards, discovered at two disparate sites between ~690-720 m and 1560-1790 m, comprise colonial (S. variabilis) and solitary (D. dianthus) scleractinians that flourished during the last ice age (~18 ka to 33 ka BP). ROV sampling (674-1815 m) spanned intermediate (Antarctic Intermediate Water) and deep waters (Upper Circumpolar Deep Water) with temperatures from ~2.5-6°C. Seawater CTD profiles of these waters show consistent physical and chemical conditions at equivalent depths between dive sites. Their carbonate chemistry indicate supersaturation (Ωcalcite ~1.3-2.2) with respect to calcite, but mild saturation to undersaturation (Ωaragonite ~0.8-1.4) of aragonite; notably some scleractinians were found living below the aragonite saturation horizon (~1000 m). Seawater δ13C and nuclear bomb produced Δ14C compositions decrease in the upper canyon waters by up to ~0.8‰ (< 800 m) and 95‰ (< 500 m) respectively, relative to measurements taken nearby in 1978, reflecting the ingress of anthropogenic carbon into upper intermediate waters.